Problemy monolitnosti morali i religii = Problems of monolithy of morality and religion = Moralʹ žәne din monolittiligi mәselesi - Agaeva, Ziba (Chabaršy. Dintanu serijasy, 2024)
The article focuses on the analysis of the relationship between morality and religion, considers the views of individual thinkers on specific features in considering the relationship between morality and religion, and considers religion as a source of moral values. It is concluded that even philosophers who studied morality and religion separately, eventually came to consider their unity, solidity. The article also analyzes the influence of morality and religion on each other. In the article, in the same perspective, the issues of the relationship between reason and faith are considered; being a form of public consciousness, the essence of the inextricable connection between these two concepts is revealed. It is concluded that established knowledge forms a rational view of the world around. At the same time, a person learns the world with the help of the surrounding world. From this point of view, faith has a branched character and, in general, is a connecting link between a person and society. In essence, faith stands above the person himself and is manifested in the existence of moral values. Man lives and creates not only for himself; he does it for the sake of others. This is the meaning of life from the point of view of faith.